Physiological and Psychological Effects of Virtual Park Therapy in Bogor City Parks on Young Adults - Prita Indah Pratiwi; Bambang Sulistyantara; Tiarie Nursya’bani Putri; Ratu Fitria; Mona Sari; Aditya Aji Pamungkas (Journal of Natural Resources and Environmental Management)
Urbanization causes limited access to nature; therefore, virtual reality (VR) is needed to stay connected to nature. This study aims to identify the physiological and psychological effects of park therapy using VR. This study was conducted using experimental methods via a VR survey. The parameters observed included physiological effects, such as heart rate and blood pressure, and psychological effects, such as mood, level of anxiety, restorativeness, and landscape perception. Profile of Mood States, State-Trait Anxiety Inventory, Perceived Restorativeness Scale, and Semantic Differential questionnaires were administered to the subject. Virtual park therapy in three locations resulted in possibly lower heart rates when walking in Bogor City Alun-alun, while lower heart rates when seated viewing in Heulang Park; decreased anger, tension, confusion, and depression after walking and decreased anger, tension, confusion, and fatigue after seated viewing, increased vigor after walking and seated viewing in all locations, decreased anxiety status after seated viewing in all locations; restorative effects of fascination, coherence, and compatibility with the highest results in Heulang Park. Sempur Park provides a therapeutic effect because it has thermal comfort and gives regularity to the psychological effect. Virtual park therapy in urban greenspaces is proven to have physiological and psychological relaxation effects.